Cognitive motivational variables and dropout intention as precursors of university dropout - López-Angulo, Yaranay; Cobo-Rendón, Rubia; Sáez-Delgado, Fabiola; Mella-Norambuena, Javier; Pérez-Villalobos, María Victoria; Díaz-Mujica, Alejandro (Frontiers in Education, 2024)
Introduction: the intention to dropout and dropout is a problem still unresolved in higher education institutions. Objective: to estimate the differences in the levels of engagement, motivation and academic satisfaction according to (a) intention to dropout and (b) students who remained with those who dropped out. Method: non-experimental designs were used. Two studies are reported, study 1 involved 3256 students and study 2 involved 2110 students. The Utrecht Work Engagement Scale Student Test, the Academic Self-Regulation Scale and the Academic Satisfaction Scale were used. The intention to dropout was measured with 3 items and the final dropout data was taken from the official register of students who dropped out of university. Results: There are significant differences in the levels of engagement, autonomous motivation and satisfaction between the students who remained and those who dropped out of the university. Discussion: Students who dropped out in the 3rd semester presented lower levels of academic engagement, motivation and academic satisfaction than those who remained. The intention to dropout and lower levels of these cognitive-motivational variables may contribute to the identification of students at high risk of dropping out. These results contribute to unveiling key variables for the educational transformation of Higher Education in the 21st century.